Word-Formation Representation of Concept FRIENDSHIP in Modern Russian - A. Aru (Научный диалог)
The features of word-formation objectification of the concept FRIENDSHIP in the Russian linguistic picture of the world are considered. The research focuses on the structure and semantics of words that form a word-formation nest with apex “friend” in Russian. It was found that the word-formative nest with the top “friend” in Russian includes 53 words. The question is raised about the verification and clarification of the cognitive features of the “Friendship” concept identified at the previous stages of the analysis. It is shown that substantive derivatives embody in conceptual block I “friendship as a feeling and attitude” such new cognitive features as “uniting someone based on friendship, unity of views, interests; cooperationʼ and friendly, benevolent attitude towards someoneʼ, and in conceptual block II the subject of friendshipʼ — such new cognitive features as ʽthe subject of marital relations (only for females)ʼ, ʽthe object that is paired with another object, forming together whole. The analysis of verb derivatives revealed a new cognitive feature for conceptual block III “friendship as a process” is a cognitive feature “to render a friendly service, to serve”. The analysis of adjective and adverbi-al derivatives helped to substantiate the need to introduce into consideration a new conceptual block IV — “quality, property, feature, characteristic of attitude / feeling of friend-ship”, in which 9 new cognitive features were found.